Development of Environmental Cleanliness Education Game for Grade 5 Students at SD Inpres Kalu - Umbu Rona Makaborang; Fajar Hariadi; Tri Sari Dewi Novyanti Bertha Mira (Journal of Artificial Intelligence and Engineering Applications (JAIEA), 2026)
Technological advances have brought major changes in various aspects of life, including the world of education. One form of use of technology in education is the development of interactive learning media such as educational games. This research aims to develop an Android-based educational game that raises the theme of environmental cleanliness and is intended for 5th grade students of SD Inpres Kalu, East Sumba. The background of this research is based on the low understanding of students on the importance of maintaining environmental cleanliness, which is caused by conventional learning methods that are less interesting and less interactive. The educational game developed will contain materials such as types of waste, how to sort and dispose of waste, and dirty environmental impacts. The research method used is research and development (R&D) with a waterfall model that includes the stages of needs analysis, design, implementation, verification, and maintenance. Supporting data were obtained through interviews, observations, and literature studies. The results of the trial showed an increase in students' understanding of environmental hygiene materials, which was evidenced by an increase in the average score from 78.0 in the pre-test to 87.2 in the post-test, with a difference of 9.2 points or an increase of 11.79%. Testing using the Black Box Testing method showed that all in-game features performed as intended, while the System Usability Scale (SUS) test results obtained an average score of 83.5, which is in the excellent category.